Approaches to Understanding Mechanisms of Dentilisin Protease Complex Expression in Treponema denticola - Goetting-Minesky, M. Paula; Godovikova, Valentina; Fenno, J. Christopher (Frontiers in Cellular and Infection Microbiology, 2021)
The oral spirochete Treponema denticola is a keystone periodontal pathogen that, in association with members of a complex polymicrobial oral biofilm, contributes to tissue damage and alveolar bone loss in periodontal disease. Virulence-associated behaviors attributed to T. denticola include tissue penetration and disruption of host cell membranes accompanied by disruption of the host cell extracellular matrix and dysregulation of host immunoregulatory factors. Dentilisin, an acylated subtilisin-family protease complex is a major virulence factor of T. denticola, is associated with several of these behaviors. Dentilisin is an outer membrane-associated complex of acylated PrtP protease and two other lipoproteins, PrcB and PrcA, all of which are encoded in a single operon consisting of prcB-prcA-prtP. PrtP is a member of the subtilase family, while PrcB and PrcA are unique to oral spirochetes. We employ multiple approaches to study mechanisms of dentilisin assembly and PrtP protease activity. To determine the role of each protein in the protease complex, we have made targeted mutations throughout the protease locus, including polar and nonpolar mutations in each gene (prcB, prcA, prtP) and deletions of specific PrtP domains. The boundaries of the divergent promoter region and the relationship between dentilisin and the adjacent iron transport operon are being resolved by incremental deletions in the sequence immediately 5’ to the protease locus. Comparison of the predicted three-dimensional structure of PrtP to that of other subtilisin-like proteases shows a unique PrtP C-terminal domain of approximately 250 residues. A survey of global gene expression in T. denticola in the presence or absence of protease gene expression reveals potential links between dentilisin and iron uptake and homeostasis in T. denticola. Understanding the mechanisms of dentilisin transport, assembly and activity of this unique may lead to more effective prophylactic or therapeutic treatments for periodontal disease.